You need to start with the identity f(x) = y, hence, substituting x + 2 for x, the graph f(x+2) = y is obtained by translating the graph f(x)=y to the left by 2 units.

Notice that f(x+2) is multiplied by -1, hence the graph of y = -f(x+2) is obtained by reflecting the graph of y=f(x+2) throuh the x axis.

Notice also that the graph of y = -f(x+2) - 5 is obtained by translating the graph of y=-f(x+2) down by 5 units.

Sketching the new graph obtained after a series of transformation were performed yields: